Genetic algorithms & engineering optimization - Gen, Mitsuo , 1944-; Cheng, Runwei (Wiley series in engineering design and automation, 2000)
"The past decade has witnessed many exciting advances in the use of genetic algorithms (GAs) to solve optimization problems in everything from product design to scheduling and client/server networking."